Pattern of ICU Patients Referred From Obstetric and Gynaecology Wards (Journal of Chittagong Medical College Teachers' Association, 2017)
Background: Management of critically ill obstetric patients in intensive care unit is a challenge. Pregnancy, delivery and puerperium can be complicated by severe maternal morbidity necessitating Intensive Care Unit (ICU) admission. So the objectives of the present study was to see the patterns of ICU referral from the obstetrics and gynaecology wards. Materials and methods: The study was conducted in Department of Obstetrics & Gynecology, of a tertiary Medical College Hospital and some Private Hospitals, Chittagong between January 2011 and December 2016. The antenatal patients (From 28 weeks onwards) and postnatal patients (Up to six weeks) who were referred to ICU were the study population. After collection data were analyzed by SPSS-20. Results: A total of 50 records kept in Gyne & Obstetrics ward. The mean age of the subjects was 27.8 ± 5.9 years and the lowest and highest ages were 18 and 40 years respectively. Majority were from rural resident (86%). Over 82% of the patients were poor and 18% middle class. The mean duration of married life of the patients was 6 ± 0.7 years and the minimum and the maximum duration were 1 year and 22 years respectively. The mean age of the last child was 2.8 ± 0.4 years and the lowest and the highest age of last child was 1 and 13 years respectively. Most (80%) of patients had a history of being pregnant 2–4 times and 18% 5–8 times and only 2% was primigravida. In terms of parity 38% of patients was primipara, 44% had 1–3 live-birth and rest 18% between 4–7 live-birth. The main causes of admission to ICU were Post Partum Haemorrhage (PPH) (42%) hypertensive disorder of pregnancy (40%) coincidental cardiac disease 4%, sepsis 6%, post cardiac arrest 4% and shock with postpartum dilated cardiomyopathy 4%. Respiratory failure and hemodynamic instability were the indication for ICU admission. Two-third (66%) of the patients was admitted in intensive care unit for respiratory failure and 46% for hemodynamic instability. For nine (98%) of 50 patients admitted to the ICU required mechanical ventilation. Conclusion: Maternal morbidity and mortality in such cases can be minimized by early assessment and aggressive intervention by a team work involving obstetricians, intensive care specialists and anesthetists.JCMCTA 2017 ; 28 (1) : 67 - 71